THE IMPACT OF VERTICAL COLLECTIVE HOUSING ON SOCIAL TRANSFORMATIONS IN CONSTANTINE CITY - Maanser Imad,; Adad Mohamed Cherif,; Bendebbache Zine, (International Journal of Innovative Technologies in Social Science, 2024)
This research examines how vertical and collective housing in Constantine city affects residents' habits, traditions, and social relationships. We investigate the impact of these space-efficient architectural models on social dynamics and urban living patterns.Vertical construction and collective housing have emerged as preferred solutions to urban housing challenges, offering pragmatic answers to urgent shelter needs. However, the transition to high-rise and communal living presents residents with a markedly different lifestyle, often conflicting with their established cultural and social norms.Our study explores this sociological shift, examining how residents adapt to their new environment in vertical and collective housing. We investigate how this transition reshapes community interactions and traditional practices within Constantine's urban fabric.